Nusantara dalam era niaga sebelum abad ke-19 - Mohammad Iskandar (Wacana: Journal of the Humanities of Indonesia, 2005)
Trading activities in the Nusantara archipelago had developed into an international trade. According to Ricklef, Europe was not the most developed region in the world. The developing world at the time was in fact the Islamic world, stretching from the Middle East to the Nusantara. If we trace it further back into the past, to the pre-Islamic age, trade in the Nusantara region had developed, espcially during the golden eras of Sriwijaya and Majapahit. This paper describes the economic and trade development in the Nusantara before the 19th century.